A systematic review of prevalence and risk factors of postpartum depression in Chinese immigrant women. Issue 6 (December 2019) - Chen, Jiarui; Cross, Wendy M.; Plummer, Virginia; Lam, Louisa; Tang, Siyuan
Abstract: Background: As the number of immigrants grows, the health of Chinese immigrant women, especially their perinatal health, has gradually attracted public attention. Our review has two main purposes. First, estimate the prevalence of postpartum depressive symptoms in Chinese immigrant women, and then determine risk factors for postpartum depressive symptoms among these women. Methods: The following databases: MEDLINE, Embase, Scopus, Web of Science, PsycINFO and PubMed were used in literature search from their commencements until November 21st 2017. The Joanna Briggs Institute (JBI) Critical Appraisal instruments were used to evaluate the quality of the article. Four studies met the inclusion criteria, contributed to our review and meta-analysis. Result: The prevalence of postpartum depression is high in Chinese immigrant women. Risk factors for postpartum depression in Chinese immigrant women were defined as lack of social support, unstable economic status, and acculturation. Conclusion: There have been few studies on postpartum depression among Chinese immigrant women. Existing studies have shown a high prevalence of postpartum depression in Chinese immigrant women. Moreover, there is an urgent need for studies on postpartum depression among Chinese immigrant women informing better understanding, programs of care and improving the perinatal health status of Chinese immigrant women.